Biogeography of the xerophytic genus Anabasis L. (Chenopodiaceae) - Lauterbach, Maximilian (Ecol Evol, 2019)
AIM: Using the extremophile genus Anabasis, which includes c. 28 succulent, xerophytic C(4) species, and is widely distributed in arid regions of Northern Africa, Arabia, and Asia, we investigate biogeographical relationships between the Irano‐Turanian floristic region (ITfr) and its neighboring regions. We test whether the spread of arid and semi‐arid biomes in Eurasia coincides with the biogeography of this drought‐adapted genus, and whether the ITfr acted as source area of floristic elements for adjacent regions. LOCATION: Deserts and semi‐deserts of Northern Africa, Mediterranean, Arabia, West and Central Asia. METHODS: Four cpDNA markers (rpL16 intron, atpB‐rbcL, trnQ‐rps16, and ndhF‐rpL32 spacers) were sequenced for 58 accessions representing 21 Anabasis species. Phylogenetic relationships and divergence times were inferred using maximum likelihood and a time‐calibrated Bayesian approach. To document the extant distribution of Anabasis, material from 23 herbaria was surveyed resulting in 441 well‐documented collections used for the coding of eight floristic regions. Using this coded data, ancestral range was estimated using “BioGeoBEARS” under the DEC model. RESULTS: Anabasis originated during the Late Miocene and the ancestral range was probably widespread and disjunct between Western Mediterranean and the Irano‐Turanian regions. Diversification started with two divergence events at the Miocene/Pliocene boundary (5.1 and 4.5 mya) leading to Asian clade I with ITfr origin which is sister to a slightly younger Asian clade II, which originated in the Western ITfr, and a Mediterranean/North African clade with an origin in the Western Mediterranean. MAIN CONCLUSIONS: Anabasis did not follow aridification and continuously expanded its distribution area, in fact its probably wide ancestral distribution area seems to have been fragmented during the very Late Miocene and the remnant lineages then expanded into neighboring arid regions. This genus supports the role of the ITfr as source area for xerophytic elements in the Mediterranean and Central Asia.